Uptake of polygenic risk information among women at increased risk of breast cancer. Issue 3 (25th December 2019) - Yanes, Tatiane; Meiser, Bettina; Kaur, Rajneesh; Scheepers‐Joynt, Maatje; McInerny, Simone; Taylor, Shelby; Barlow‐Stewart, Kristine; Antill, Yoland; Salmon, Lucinda; Smyth, Courtney; Young, Mary‐Anne; James, Paul A.
Abstract: Polygenic risk scores (PRSs) are increasingly being implemented to assess breast cancer risk. This study aimed to assess and determine factors associated with uptake of PRS among women at increased risk of breast cancer for whom genetic testing to date had been uninformative. Participants were recruited from the Variants in Practice study from which breast cancer PRS had been calculated. Four hundred women were notified by letter of the availability of their PRS and invited to complete a self‐administered survey comprising several validated scales. Considering non‐participants, uptake of PRS was between 61.8% and 42.1%. Multivariate logistic regression identified that women were more likely to receive their PRS if they reported greater benefits (odds ratio [OR] = 1.17, P = .011) and fewer barriers to receiving their PRS (OR = 0.80, P = .007), had completed higher level education (OR = 3.32, P = .004), and did not have daughters (0.29, P = .006). Uptake of breast cancer PRS varied according to several testing‐ and patient‐related factors. Knowledge of these factors will facilitate the implementation of polygenic testing in clinical practice and support informed decision making by patients. Abstract :